The Influence of Auditor’s Intrinsic and Extrinsic Factors on Audit Quality - Sigit Handoyo; Reny Lia Riantika; Muhammad Irfan Hidayat (AFRE (Accounting and Financial Review), 2022)
This study aims to determine whether independence, competence, professional skepticism, audit structure and role stress affect audit quality. This research was conducted on auditors who work at the Financial and Development Supervisory Agency (BPKP) RI Representatives of the Special Region of Yogyakarta (DIY). This study uses non-probability sampling and obtained a sample of 34 people. Data was collected using a questionnaire method distributed to respondents. The results of this study indicate that independence, competence, professional skepticism and audit structure partially have a positive and significant effect on audit quality. Meanwhile, role stress (role conflict and role ambiguity) has a negative effect on audit qualityDOI: https://doi.org/10.26905/afr.v5i2.7808